Mechanical, Thermal Stability and Water Absorption Properties of Recycled Thermoplastic Blend Nanocomposites: Comparison of Nanoclay and Carbon Nanotube - Nor Arman, Nur Syafiqaz; Chen, Ruey Shan; Ahmad, Sahrim (International Journal of Integrated Engineering, 2022)
This present paper investigates the influence of clay (Cloisite 10A) and multiwalled carbon nanotubes (MWCNT) loading for the tensile, flexural, thermal stability and water absorption properties of recycled thermoplastic blend made from recycled high-density polyethylene (rHDPE) and recycled polyethylene terephthalate (rPET). The nanocomposites were prepared via extrusion blending technique by using extruder and compressed using hot and cold press molding machine. The findings showed that the sample with 1 phr of Cloisite 10A and 4 phr of MWCNT showed the optimum of tensile strength at 13.9 MPa and 14.5 MPa as compared to other loadings. The flexural strength exhibited inconsistent trend with the increasing of Cloisite 10A and MWCNT content. The addition of Cloisite 10A and MWCNT-reinforced nanocomposite showed better thermal stability than pure polymer blend. As the increment of Cloisite 10A and MWCNT loading, the percentages of water uptake increased but the values were still lower than the neat thermoplastic blend.